Critical success factors for the management of 4x4 ecotrails - M. Saayman; C. A. Klaibor (South African Journal of Business Management, 2016)
In South Africa, 4x4 ecotrails that fall into the adventure tourism category are increasing in popularity. The purpose of this study is to compile a profile of 4x4 trail users, identify their motives and then determine critical success factors (CSFs) for the management of 4x4 trails. The comprehension of the coherence between the travel motives that lead to a visit and the CSFs that determine whether visitors are satisfied and have gained a memorable experience (which should lead to repeat visits) is examined in this research. An online survey was conducted in South African National Parks and the focus was on ecotrails, which contribute to nature conservation and provide maximum sustainability. A total of 119 questionnaires were obtained. The results found seven motivations and CSFs, respectively, revealing two new motivational factors within this context (lifestyle and spiritual well-being) and three new CSFs that have not been identified before and put a clear focus on the trail itself (interpretation, trail planning and challenging experience). This information can be used by trail managers and marketers to reach this niche market and provide visitors with a memorable experience.
Keywords: 650